2018
DOI: 10.1111/bph.14122
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of CYP1B1 in interferon γ‐induced alterations of epithelial barrier integrity

Abstract: These data suggest that increased expression of CYP1B1 is involved in the effects of IFNγ on epithelial permeability. Inhibition of CYP1B1 counteracts the alterations of epithelial barrier integrity induced by IFNγ and could thus have a therapeutic potential in disorders of intestinal permeability associated with inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 67 publications
1
3
0
Order By: Relevance
“…Further, it reveals that upregulated CYP1A1 and CYP1B1 expression is preserved during inflammatory crosstalk between Wnt5A and proinflammatory IL-1β in human coronary artery endothelial cells. This novel finding from human vascular endothelial cells isolated from coronary artery, a primary cell system retaining original tissue characteristics (Franscini et al, 2004;Skaria et al, 2019), is in accordance with previous findings that proinflammatory cytokines, in contrast to their suppressive effects on drug metabolizing pathways in hepatocytes (Morgan, 2009;Wu and Lin, 2019), stimulate the transcription of CYP enzymes in extrahepatic cell systems (Smerdová et al, 2014;Alhouayek et al, 2018). Previous studies showed that CYP1A1, involved in transformation of xenobiotics to toxic metabolites, also metabolizes a broad spectrum of drugs and consequently account for drugs' adverse effects.…”
Section: Discussionsupporting
confidence: 91%
“…Further, it reveals that upregulated CYP1A1 and CYP1B1 expression is preserved during inflammatory crosstalk between Wnt5A and proinflammatory IL-1β in human coronary artery endothelial cells. This novel finding from human vascular endothelial cells isolated from coronary artery, a primary cell system retaining original tissue characteristics (Franscini et al, 2004;Skaria et al, 2019), is in accordance with previous findings that proinflammatory cytokines, in contrast to their suppressive effects on drug metabolizing pathways in hepatocytes (Morgan, 2009;Wu and Lin, 2019), stimulate the transcription of CYP enzymes in extrahepatic cell systems (Smerdová et al, 2014;Alhouayek et al, 2018). Previous studies showed that CYP1A1, involved in transformation of xenobiotics to toxic metabolites, also metabolizes a broad spectrum of drugs and consequently account for drugs' adverse effects.…”
Section: Discussionsupporting
confidence: 91%
“…The cytochrome P450 (CYP) family 1 enzymes are mainly controlled by aryl hydrocarbon receptor (AhR), which is involved in phase I xenobiotic metabolism in the intestine 32 . Induction of CYP1A1 and CYP1B1 enhances inflammatory responses and alters the intestinal epithelial barrier function 33 , 34 . Consistent with previous findings that azo dyes can induce CYP1 enzymes 35 , AhR was activated (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…After binding with the ligand, AhR translocates to the nucleus and binds with AhR nuclear translocator, forming a heterodimer, which modulates the target gene (CYP1A2) expression through binding with xenobiotic-responsive elements [54,55]. It is also found that downregulation of CYP1A2 is observed during inflammation [56], whereas AhR activation protects intestinal epithelium from enterocolitis by promoting CYP1A2 expression [57][58][59], and that indole derivatives activate AhR to promote IL-22 secretion, which boosts intestinal mucosal defense [60]. Interestingly, the present study found a significantly elevated expression of AhR, CYP1A2, and IL-22 in the jejunum of the FMT group, indicating that gut microbiota (probably Lactobacillus)-produced metabolites protect jejunum from inflammation and promote intestinal homeostasis.…”
Section: Discussionmentioning
confidence: 99%